PENGARUH KEMAMPUAN KONEKSI MATEMATIS TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Wati, Mira; Medika, Gema Hista; Junaidi, Junaidi (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This research was conducted to know connection between Mathematic Connection and Students’ Problem Solving Capability on Mathematic. This research was a correlational Sample collection and was done by random sampling with doing normality testing in the beginning and homogeneity testing in population date. The sample was approximately 23 students from 117 populations. This research used T-testing to find the meaning of the regression.”Simple Regression-equation for”connection ability towards students’”problem solving”ability on mathematics was Y= 0,536 + 0,768X by correlation 0,760 and KP 57,829%. Hypothesis-testing result was gained tcounting= 5,366 and ttable= 1,71. It is concluded that there is a connection between Mathematic Connection to Students’ Problem Solving Capability on Mathematic in Grade VIII SMPN 3 Palembayan.